HDL with digital design : VHDL and Verilog - Botros, Nazeih, 1945- (Mercury Learning and Information, 2015)
This book introduces the latest version of hardware description languages and explains how the languages can be implemented in the design of the digital logic components. In addition to digital design, other examples in the areas of bioengineering and basic computer design are covered. It introduces mixed language programming by covering both Verilog and VHDL side by side. Students, as well as professionals, can learn both the theoretical and practical concepts of digital design. The two languages are equally important in the field of computer engineering and computer science as well as other engineering fields such as simulation and modeling. This resource uses the latest versions of both Verilog and VHDL; includes fundamentals of synthesis and FPGAs implementation; instructor's resources available upon adoption. -- Edited summary from book.
Includes index.
Keywords: Computer hardware description languages.; VHDL (Computer hardware description language); Verilog (Computer hardware description language); Integrated circuits -- Design and construction -- Data processing.; elektronické knihy; electronic books